Mosaic loss of chromosome Y in blood is associated with Alzheimer disease - Dumanski, J; Lambert, J; Rasi, C; Giedraitis, V; Davies, H; Grenier-Boley, B; Lindgren, C; Campion, D; Dufouil, C; Pasquier, F; Amouyel, P; Lannfelt, L; et al. (Cell Press, 2016)
Men have a shorter life expectancy compared with women but the underlying factor(s) are not clear. Late-onset, sporadic Alzheimer disease (AD) is a common and lethal neurodegenerative disorder and many germline inherited variants have been found to influence the risk of developing AD. Our previous results show that a fundamentally different genetic variant, i.e., lifetime-acquired loss of chromosome Y (LOY) in blood cells, is associated with all-cause mortality and an increased risk of non-hematological tumors and that LOY could be induced by tobacco smoking. We tested here a hypothesis that men with LOY are more susceptible to AD and show that LOY is associated with AD in three independent studies of different types. In a case-control study, males with AD diagnosis had higher degree of LOY mosaicism (adjusted odds ratio = 2.80, p = 0.0184, AD events = 606). Furthermore, in two prospective studies, men with LOY at blood sampling had greater risk for incident AD diagnosis during follow-up time (hazard ratio [HR] = 6.80, 95% confidence interval [95% CI] = 2.16-21.43, AD events = 140, p = 0.0011). Thus, LOY in blood is associated with risks of both AD and cancer, suggesting a role of LOY in blood cells on disease processes in other tissues, possibly via defective immunosurveillance. As a male-specific risk factor, LOY might explain why males on average live shorter lives than females.